A Collaborative Learning Framework & Serious Game Development - CORRIGAN, SIOBHAN; MCDONALD, NICHOLAS; Zon, G.D.R.; Maij, A.; Mårtensson, L. (My University, 2015)
This paper presents the overall learning process that evolved during the MASCA project (MAnaging System Change in Aviation—EU FP7 funded project (2010–2013), specifically focusing on the one of the key elements of the overall learning approach, the development of a serious game (SKYBOARD) and the role the game played in supporting the implementation of airport collaborative decision-making (A-CDM) in a major European airport. The underlying principles of the learning process was based on ongoing and collaborative learning in the workplace, with each phase of learning involving preparation and guidance, collaborative learning, consolidation of that learning and practically focused next steps that can be deployed to support overall change management. The aim of SKYBOARD was to aid communication and collaboration when introducing A-CDM, and thereby supporting the cultural change that comes with this introduction. The development of SKYBOARD was based upon an initial training needs analysis and an iterative development and implementation approach at a major European airport. The research demonstrated that we are at the beginning of a fundamental shift in the way both learning and working is happening in organisations. Therefore, the establishment of a collaborative learning process and integrated learning package needs to focus on supporting continuous performance improvement and learning (competency and capability at all levels) and to ensure this overall learning is fully aligned to the overall strategic blueprint of the organisation. The evaluation of SKYBOARD demonstrated that serious games can support collaborative learning and enhanced communication and that such games should be key resource in any learning environment and proved to be a highly effective support to the implementation of A-CDM in this case.
PUBLISHED
Keywords: Collaborative learning process; Serious games; SKYBOARD; Airport Collaborative Decision Making (A-CDM); Intelligent Content & Communications; Aerospace psychology